A study on jet impingement behaviour - New, Chee Siong. (2012)
Impinging jet is a very popular method to enhance heat transfer from or to surfaces. In the past, there were extensive studies on the dynamics of jet impingement on flat surface but only a few on cylindrical surfaces. Therefore, this project aimed to study the dynamics of jet impingement on convex surface through flow visualization of different configuration. Dye-visualization was used to investigate the behaviour of a round jet issuing from a nozzle and impinging on cylindrical surfaces at different Reynolds numbers. Effects of cylinder diameter, nozzle-to-surface distance, Reynolds number of jet flow, cylinder with inclination and position of cylinder offset from neutral jet axis on the jet flow structure would be further tested and described.